Wages and Unemployment in a Poor Agrarian Economy: A Theoretical and Empirical Analysis - Bardhan, Pranab K. (Journal of Political Economy, 1979)
In much of the theoretical literature on development the standard assumption is that of a constant wage in agriculture. In this paper we cite some evidence, obtained in our detailed analysis of a recent large-scale survey of rural labor households by the National Sample Survey in India, of how the existing theories of wage determination by biological or institutional factors leave much to be explained in terms of the observed data. We then proceed to construct a modified theoretical framework which generate comparative-static hypotheses which seem to be consistent with many of the stylized facts.